2020
DOI: 10.1111/tme.12707
|View full text |Cite
|
Sign up to set email alerts
|

Fertility and pregnancy in Iranian thalassemia patients: An update on transfusion complications

Abstract: Background: Despite the significant advances in thalassemia pathobiology and efficacy of chelation regimens, complications of transfusion therapy have attenuated the reproductive health of thalassemia patients. Depending on clinical profiles, we aimed to assess the fertility status and stresses among thalassemia patients who desired to have children. Material and methods: A total of 213 couples in reproductive ages were enrolled in this study in Tehran. Patients' demographic, clinical, fertility and spouse's h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Genes HBB and HBD encode hemoglobin subunits β and δ. Their deficiency is associated with thalassemia, a contributing factor of poor reproductive potential in women (Takhviji et al, 2020). Human hemoglobin deficiency is consistent with hemoglobin underexpression in dogs (Yang X. et al, 2018) and domestic chickens (Fallahshahroudi et al, 2019) when compared with the most recent common ancestors for their wild counterparts (see Table 4).…”
Section: Resultsmentioning
confidence: 70%
“…Genes HBB and HBD encode hemoglobin subunits β and δ. Their deficiency is associated with thalassemia, a contributing factor of poor reproductive potential in women (Takhviji et al, 2020). Human hemoglobin deficiency is consistent with hemoglobin underexpression in dogs (Yang X. et al, 2018) and domestic chickens (Fallahshahroudi et al, 2019) when compared with the most recent common ancestors for their wild counterparts (see Table 4).…”
Section: Resultsmentioning
confidence: 70%
“…Human gene HBD produces hemoglobin subunit δ, a deficit of which (thalassemia) is clinically proven as a risk factor for auto-aggressive impulsiveness up to suicide [64], female subfertility [65], under-threshold IQ, and severe anxiety in children [66], as readers can see in Table 8. Actually, both suicide and IQ look like human-specific traits, which are biomedically studied mostly in human behavioral models based on animals [67,68] and are not common in the wild [56].…”
Section: Discussionmentioning
confidence: 99%
“…This finding fits the first principal component (PC1) explaining two-thirds (67%) of the differential-gene-expression variance during the domestication-related microevolution (Figures 3 and 4a). With this in mind, we suggest HBD as a candidate gene contributing to self-domestication syndrome, namely: low HBD expression might be regarded as what humans pay with health (e.g., higher risks of suicide [64], female subfertility [65], low IQ, and anxiety in children [66]) for the benefits received during evolution (e.g., the ability to build trust [69][70][71], prevention of injuries [72], and making adequate decisions under stress [74]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thalassemia affects women's fertility. Iron overload impairs the hypothalamic-pituitaryovarian axis, which explains why the concentration of ferritin inversely correlates with reproductive hormone concentrations in thalassemic women [136]. Takhviji et al thus suggested that iron chelation, especially during puberty, could be beneficial for patients with thalassemia to increase fertility [136].…”
Section: Thalassemiamentioning
confidence: 99%